2019
DOI: 10.1177/0300060519847854
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA-NEF is downregulated in postmenopausal osteoporosis and is related to course of treatment and recurrence

Abstract: Objectives We investigated the role of long non-coding (lnc) RNA-NEF (neighboring enhancer of FoxA2), a characterized oncogene in cancer biology, in postmenopausal osteoporosis and its diagnostic and prognostic value in this disease. Methods Expression of lncRNA-NEF in plasma was detected by RNA extraction and real-time quantitative PCR. The diagnostic value of lncRNA-NEF and interleukin (IL)-6 for postmenopausal osteoporosis was evaluated by receiver operating characteristic curve analysis, with postmenopausa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 15 publications
0
17
0
Order By: Relevance
“…In this study, we found that OG may activate VEGFA, EGFR, and MAPK1, as their binding a nities for interaction were all <-7.0. Furthermore, IL6 and IL2 are involved not only in in ammatory responses but also in the regulation of bone mineral density, osteoclast differentiation and activation [40][41]. However, our molecular docking results for IL6 and IL2 showed binding a nities of -6.7 and − 6.1 kcal•moL − 1 ; these are higher than − 7.0 kcal•moL − 1 and therefore indicate that OG exerts only weak inhibition on in ammatory responses.…”
Section: Discussionmentioning
confidence: 68%
“…In this study, we found that OG may activate VEGFA, EGFR, and MAPK1, as their binding a nities for interaction were all <-7.0. Furthermore, IL6 and IL2 are involved not only in in ammatory responses but also in the regulation of bone mineral density, osteoclast differentiation and activation [40][41]. However, our molecular docking results for IL6 and IL2 showed binding a nities of -6.7 and − 6.1 kcal•moL − 1 ; these are higher than − 7.0 kcal•moL − 1 and therefore indicate that OG exerts only weak inhibition on in ammatory responses.…”
Section: Discussionmentioning
confidence: 68%
“…LncRNA-Neighboring enhancer of FOXA2 (NEF), which is known to the inhibit Wnt/β-catenin signaling and transforming growth factor-ßTGF-β pathways in cancer cells (Liang et al, 2018;Ju et al, 2019) is also reported in postmenopausal osteoporosis (PMOP) patients in a high concentration. In human BMSCs isolated from PMOP, enforced expression of NEF inhibited the secretion of IL-6, indicating its potential not only in diagnostics, but also as a prognostic biomarker for PMOP (Ma et al, 2019).…”
Section: Lncrnas In Bone Mesenchymal Stem Cell Regulationmentioning
confidence: 99%
“…lncRNA-NEF may play a role in osteoporosis by inhibiting IL-6. Studies in postmenopausal osteoporosis showed that a high lncRNA-NEF level was associated with a substantially reduced course of treatment and lower post-treatment recurrence rate [93]. lncRNA NONMMUT037835.2 regulated osteoclastogenesis by negatively regulating RANK expression and inhibiting the NF-κB/MAPK signaling pathway.…”
Section: Lncrna-mediated Mechanismsmentioning
confidence: 99%